2013
DOI: 10.4314/jae.v16i2.15
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Perception and Adaptation Strategies to Climate Change among Farmers in Southern Agricultural Zone of Nasarawa State, Nigeria

Abstract: Climate change is perhaps the most serious environmental threat facing mankind worldwide. The study was designed to assess the knowledge, perception and adaptation strategies to climate change among farmers in southern agricultural zone of Nasarawa state. The specific objectives were to: identify the sources of information on climate change by respondents; assess their knowledge and perception of climate change phenomenon; identify adaptation strategies used and the factors militating against their adaptive ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 3 publications
1
10
0
Order By: Relevance
“…Similar coping strategies were reported from various studies conducted in different parts of Africa like Ethiopia, South Africa and Nigeria (Giorgis et al, 2006;Hassan & Nhemachena, 2008;Salau, 2012). Adaptive capacity of smallholder farmers to changes in climatic events is usually low due to dependence on natural resources, constraints in human and physical capital, and poor infrastructure (Shewmake, 2008;Salau, 2012;Gukurume, 2013). In this survey, factors that hindered adaptation included poverty (inability to pay for farm inputs, equipment and services like labor), unreliable weather forecasts, and shortage of food to store, among others.…”
Section: Effect Of Climate Change On Crop Productionsupporting
confidence: 60%
See 1 more Smart Citation
“…Similar coping strategies were reported from various studies conducted in different parts of Africa like Ethiopia, South Africa and Nigeria (Giorgis et al, 2006;Hassan & Nhemachena, 2008;Salau, 2012). Adaptive capacity of smallholder farmers to changes in climatic events is usually low due to dependence on natural resources, constraints in human and physical capital, and poor infrastructure (Shewmake, 2008;Salau, 2012;Gukurume, 2013). In this survey, factors that hindered adaptation included poverty (inability to pay for farm inputs, equipment and services like labor), unreliable weather forecasts, and shortage of food to store, among others.…”
Section: Effect Of Climate Change On Crop Productionsupporting
confidence: 60%
“…In countries like Senegal, China, Ghana, Nepal, Bangladesh, Nigeria, United States of America, farmers have been mentioned to perceive and even adapt to changes in the climate (Mertz et al, 2009;Byg & Salick, 2009;Fosu-Mensah et al, 2010;Maharjan et al, 2011;Haque et al, 2011;Salau, 2012;Arbuckle et al, 2013). Socioeconomic and environmental factors have been demonstrated in various studies to influence farmers' perception and adaptation to changes in the climate (Deressa et al, 2011), those include education, household size, livestock ownership, agro-ecological zone, farm size and access to credit among others.…”
Section: Introductionmentioning
confidence: 99%
“…The average extension visit to the respondents was once in a year. This indicates that extension service delivery is far below the recommended schedules as Salau et al (2012) reported that the recommended visit schedules of village extension agents under the T&V system is two extension visit per month. On the average, the women have been engaged in groundnut processing for 13 years indicating that they have many years of processing experience.…”
Section: Methodsmentioning
confidence: 96%
“…First, the Cardamom Development Center alone cannot fulfill farmers' needs. Community-level institutions are essential to smooth service delivery and have the best potential to strengthen farmers' capacity through extension services and provision of agricultural inputs (Salau, Onuk, & Ibrahim, 2012).…”
Section: Prescription: Assessment Of Institutional Interaction and Political Economymentioning
confidence: 99%